THE RELEVANCE OF INTEGRATED ISLAMIC EDUCATION IN BUILDING NATION CHARACTERS IN THE DIGITAL 4.0 ER - Rifa’I, Ahmad; Choli, Ifham (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2019)
Islamic religious education is one of the main components in shaping the character and personality of the nation. In this digital era 4.0 where particular communication has become universal, Islamic religious education must be able to become a spirit that directs technology so that it is always useful in human life. This study aims to find ways to integrate Islamic religious education with science and technology that can improve the character building of the nation. The research methodology used in this study is a qualitative descriptive research method that describes the current conditions of Islamic religious education learning and its relation to the nation's character building. The result of this research is that Islamic religious education should not be monolithic but must be integrated with non-religious subjects as well as science and technology so that today's young generation are willing and interested in studying religion well and Islamic religious education can be of value. which colors every skill and profession of Indonesian citizens, so that the morals and morals of the nation develop well according to the example of the Prophet Muhammad and aspired to by the state.